DOES GRAVES- DISEASE AFFECT ESOPHAGEAL MOTILITY? - TURGUT, SEDA; Senturk, H; ŞENTÜRK, HAKAN; Karaman, Ö; İlhan, M; Turgut, SEDA; Arabaci, E; Taşan, E (My University, 2018)
Context: The gastrointestinal tract is one of the most affected systems in hyperthyroidism. Although thyrotoxicosis is thought to be associated with gastrointestinal dysmotility, there are limited studies focused on motility disorders in hyperthyroidism. Objectives: We aimed to investigate the manometric measurements to determine if esophageal motility is affected in Graves' disease. Materials and methods: Thirty patients with Graves' disease (18 female and 12 male) and 30, age and sex matched, healthy controls (22 female and 8 male) were recruited to the study between 2015 and 2016. Esophageal manometry was performed using MMS (Medical Measurement Systems bv. The Netherlands) Solar GI - Air Charged Intelligent Gastrointestinal Conventional Manometry. Results: The mean lower esophageal sphincter pressure (LESP) was 16.9 ± 5.3 mmHg in hyperthyroid patients and 20.1 ± 8.8 mmHg in the control group and there was no significant difference (p>0.05). It was observed that the duration of contraction was 3.9 ± 0.7 s in healthy subjects and, significantly shorter 3.2 ± 0.5 s in hyperthyroid patients (p<0.001). Duration of contraction was negatively correlated with TSH receptor Ab titer in patients (p=0.006, r= -0.48). Also, it was observed that the duration of relaxation was negatively correlated with fT4 levels in the patient group (p<0.05, r= -0.46). Conclusion: In this study, we observed that esophageal motility can be affected via shortened duration of contraction in Graves' disease. The gastrointestinal symptoms due to possible motility dysfunctions should be considered in the evaluation of hyperthyroid patients.